Development of Science Worksheet Based on Multiple Intelligences with Guided Inquiry Model to Improve Critical Thinking Skills of Elementary School Students - Budiman, Pramesti Mayaza; Sri Haryani; Tri Suminar (Universitas Negeri Semarang, 2024)
The rapid advancement of information technology characterizes 21st-century education. In addition to cognitive, affective, and psychomotor aspects, 21st-century learning also requires students to develop several skills known as the 4Cs: Communication, Collaboration, Critical Thinking, and Creativity. This study aims to develop Student Worksheets (LKPD) that produce Science Worksheets based on Multiple Intelligences with the Guided Inquiry model, which meet the criteria of being appropriate and effective in improving students' critical thinking skills. This research is a Research and Development (R&D) study that adopts the 4D development model, which includes the stages of definition, design, development, and dissemination. Data collection techniques used in this study include interviews, observations, questionnaires, tests, and documentation. This research involved 90 students divided into two groups: a small group and a large group. The validation results of the LKPD were rated as highly feasible by the validators, with an average score of 97,7% in the media aspect, 98% in the material aspect, and 98,9% in the language aspect. The LKPD also improved students' critical thinking skills, with an average difference between pretest and posttest scores of 16.33 and an N-gain score of 0.504 in the large group trial, which falls into the medium criteria. Therefore, developing Science Worksheets based on Multiple Intelligences with the Guided Inquiry model is feasible and effective in improving students' critical thinking skills.